Violence, Silence, and Stigma: A Public Theology of Crucifixion as Torture - Tombs, D. (University of jaffna, 2024)
In this presentation, I discuss how reports like Human Rights Watch, We Will Teach You a Lesson: Sexual Violence against Tamils by Sri Lankan Security Forces (2013), can inform a public theology of crucifixion as torture. I argue that theological attention to torture reports can (1) deepen an informed understanding of the experiences of contemporary political prisoners, and (2) offer insights into the historical experience of Jesus. The report ‘We Will Teach You a Lesson’ is particularly confronting because it focusses on testimonies of sexual violence (or ‘sexualised violence’) during the torture of Tamil prisoners in detention from 2006-2012. In the open access book, The Crucifixion of Jesus: Torture, Sexual Abuse, and the Scandal of the Cross (https://doi.org/10.4324/9780429289750), I examine the evidence for believing Jesus experienced sexualised violence during his detention and crucifixion. Jesus’ historical experience of torture provides a compelling theological reason for giving reports like We Will Teach You a Lesson serious attention in public theology. I argue that torture reports can contribute to a public theology of torture by offering important insight into Roman crucifixion as a form of torture, an instrument of state terror, and an open opportunity for sexualised violation. We Will Teach You a Lesson shows that sexual violation against both male and female prisoners during torture was common. In addition, the report notes that sexual violence is often highly stigmatised and information on sexual violation is rarely volunteered by victims; when torture is mentioned, victims often use indirect language or euphemisms. I argue that greater awareness of silence, reticence, and indirect referencing, is therefore important when reading the biblical texts of Jesus’ torture.
Keywords: Jesus and sexualised violence; Roman crucifixion; Public theology of crucifixion as torture